THE EFFORTS OF APPLICATION OF THE TRADITIONAL ENGKLEK GAME TO IMPROVE THE Rough Motors of EARLY CHILDREN IN TK B AISYIYAH AL AMIN BIBIS LUHUR THE ACADEMIC YEAR 2022 - Fenti Risti Saputri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This study aims to develop children's gross motor skills through the traditional engklek game. The method used in this research is descriptive qualitative method. The data collection techniques in this research are: Interview, observation and documentation. engklek with and they are more familiar with traditional games. Aisyiyah Al Amin Kindergarten teachers can work together to guide children in formulating clear goals in the learning process using the traditional engklek game. children and observing the results are very satisfying where the children have done engklek game activities, the results of 14 of the 18 students who became the subject of gross motor research have developed well.Keywords: Children's Gross Motoric, Traditional Games, Engklek